2021
DOI: 10.1039/d0cb00236d
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinker-modified nucleic acid probes for improved target identification and biomarker detection

Abstract: Crosslinker-modified nucleic acid probes are promising substitutes for regular oligonucleotide probes in hybridization-based assays, as they allow a more selective and efficient detection of nucleic acid targets and nucleic acid biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Molecular modeling studies indicated that photochemical [2 + 2] cycloaddition is facilitated with the orientation of the vinyl group of CNV K to be stacked onto the C5–C6 double bond of pyrimidine nucleobases located at the −1 position on the complementary strand (see above). 104,111 Overall, crosslinking stabilizes the oligonucleotide duplexes. 14,108,111 The impacts of the photoconvertible groups on duplex stabilities before crosslinking reaction were also investigated by the Fujimoto group.…”
Section: Photochemical Modifications For Dna/rna Oligonucleotidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular modeling studies indicated that photochemical [2 + 2] cycloaddition is facilitated with the orientation of the vinyl group of CNV K to be stacked onto the C5–C6 double bond of pyrimidine nucleobases located at the −1 position on the complementary strand (see above). 104,111 Overall, crosslinking stabilizes the oligonucleotide duplexes. 14,108,111 The impacts of the photoconvertible groups on duplex stabilities before crosslinking reaction were also investigated by the Fujimoto group.…”
Section: Photochemical Modifications For Dna/rna Oligonucleotidesmentioning
confidence: 99%
“…Although psoralen is widely used as a thymine-selective photo-crosslinker in biological studies, there are limitations such as requiring a TpA step in the sequence and causing photodamage to DNA by forming pyrimidine photodimers upon cycloreversion that uses UV-C (254 nm). 104,106 To alleviate these issues, Fujimoto et al, reported 3-cyanovinylcarbazole nucleoside ( CNV K) as a reversible photo-crosslinker that can photo-crosslink to pyrimidine base located 5 0 to the complementary base through [2 + 2] cycloaddition with 385 or 365 nm irradiation (Fig. 12).…”
Section: Carbazolementioning
confidence: 99%
See 1 more Smart Citation
“…The cross-linked dumbbell ODNs were developed as potential decoy molecules with an NF-κB binding ability . In addition, various types of cross-linking reactions to the native RNA have been developed to form the stable complex, inhibit the gene expression, capture the target RNA, and fluorescently label RNA. As other applications, the cross-linking reaction was utilized in the DNA-encoded dynamic library and DNA origami. …”
Section: Introductionmentioning
confidence: 99%
“… 13 15 If a probe modified using a CNV-K is cross-linked with a target nucleic acid, the probe can maintain its binding state with the target nucleic acid even after the dissociation of hydrogen bonds. 16 This technology enables the use of washing procedures using denaturing agents and surfactants to remove nonspecific adsorbents. It also prevents the loss of target nucleic acids due to dissociation from the probe during magnetic separation and processes other than washing.…”
Section: Introductionmentioning
confidence: 99%